MHealth tool to improve community health agent performance for child development: study protocol for a cluster-randomised controlled trial in Peru. Issue 11 (6th November 2019) - Westgard, Christopher Michael; Rivadeneyra, Natalia; Mechael, Patricia
Abstract : Introduction: Cultivating child health and development creates long-term impact on the well-being of the individual and society. The Amazon of Peru has high levels of many risk factors that are associated with poor child development. The use of 'community health agents' (CHAs) has been shown to be a potential solution to improve child development outcomes. Additionally, mobile information and communication technology (ICT) can potentially increase the performance and impact of CHAs. However, there is a knowledge gap in how mobile ICT can be deployed to improve child development in low resource settings. Methods and analysis: The current study will evaluate the implementation and impact of a tablet-based application that intends to improve the performance of CHAs, thus improving the child-rearing practices of caregivers and ultimately child health and development indicators. The CHAs will use the app during their home visits to record child health indicators and present information, images and videos to teach key health messages. The impact will be evaluated through an experimental cluster randomised controlled trial. The clusters will be assigned to the intervention or control group based on a covariate-constrained randomisation method. The impact on child development scores, anaemia and chronic malnutrition will be assessed with an analysis of covariance. The secondary outcomes include knowledge of healthy child-rearing practices by caregivers, performance of CHAs and use of health services. The process evaluation will report on implementation outcomes. The study will be implemented in the Amazon region of Peru with children under 4. The results of the study will provide evidence on the potential of a mHealth tool to improve child health and development indicators in the region. Ethics and dissemination: The study received approval from National Hospital 'San Bartolome' Institutional Ethics Committee on 8 November 2018 (IRB Approval #15463–18) and will be disseminated via peer-reviewed publications. Trial registration number: ISRCTN43591826 .